Pathogenic and Potential Therapeutic Roles of Exosomes Derived From Immune Cells in Liver Diseases - Zhou, Leyu; Shen, Mengyi; Fan, Xiaoli; Liu, Yifeng; Yang, Li (Frontiers in Immunology, 2022)
Liver diseases, such as viral hepatitis, alcoholic hepatitis and cirrhosis, nonalcoholic steatohepatitis, and hepatocellular carcinoma place a heavy burden on many patients worldwide. However, the treatment of many liver diseases is currently insufficient, and the treatment may be associated with strong side effects. Therapies for liver diseases targeting the molecular and cellular levels that minimize adverse reactions and maximize therapeutic effects are in high demand. Immune cells are intimately involved in the occurrence, development, and prognosis of liver diseases. The immune response in the liver can be suppressed, leading to tolerance in homeostasis. When infection or tissue damage occurs, immunity in the liver is activated rapidly. As small membrane vesicles derived from diverse cells, exosomes carry multiple cargoes to exert their regulatory effects on recipient cells under physiological or pathological conditions. Exosomes from different immune cells exert different effects on liver diseases. This review describes the biology of exosomes and focuses on the effects of exosomes from different immune cells on pathogenesis, diagnosis, and prognosis and their therapeutic potential in liver diseases.